Upward trend in follicular lymphoma among the Korean population: 10-year experience at a large tertiary institution - Kim, Meejeong; Hwang, Hee Sang; Cho, Hyungwoo; Yoon, Dok Hyun; Suh, Cheolwon; Park, Chan Sik; Go, Heounjeong; Huh, Jooryung (Journal of pathology and translational medicine, 2021)
Background: Follicular lymphoma (FL) is the second most common non-Hodgkin lymphoma (NHL) in Western countries. However, it is relatively rare in Asia. This study examined epidemiologic characteristics of FL in South Korea, with an emphasis on recent trends of increase in cases. Methods: We retrospectively examined 239 cases of newly diagnosed FL at a large tertiary institution in Korea (Asan Medical Center, Seoul, Republic of Korea) between 2008 and 2017. Age-adjusted incidence rates and clinicopathological variables were analyzed, and joinpoint regression analysis was used to identify the changes. Results: The age-adjusted incidence of FL significantly increased during the study period (p = .034), and the ratio of (relative incidence) patients with FL to patients with NHL increased from 4.28% to 9.35% in the same period. Over the 10-year study assessment duration, the proportion of patients with stage III/IV FL (p = .035) and expression of BCL2 (p = .022) or BCL6 (p = .039) significantly increased. From 2013–2017, the proportion of patients with highrisk Follicular Lymphoma International Prognostic Index (FLIPI) score increased (21.5% to 28.7%), whereas that of low-risk FLIPI decreased (55.4% to 38.6%), although those results were not statistically significant (p = .066). Conclusions: We found an increasing incidence of FL, with a disproportionate increase in the incidence of high-stage disease and recent changes in the clinicopathologic features of the Korean patient population.